Intranasal and Intravenous Administration of Desmopressin: Effect on F VIII/vWF, Pharmacokinetics and Reproducibility - Lethagen, S; Harris, A S; Sjörin, E; Nilsson, I M (Thrombosis and Haemostasis, 1987)
A comparison was made of intranasal administration of 300 μg desmopressin (DDAVP) by spray, with intravenous administration of 0.2, 0.3 and 0.4 μg DDAVP/kg in 10 healthy volunteers. The effect of DDAVP was measured on F VIII/vWF complex and on plasminogen activator release. In addition, plasma levels of DDAVP were determined using a specific and sensitive radioimmunoassay. Moreover, the reproducibility of the spray effect in 10 healthy volunteers was tested after administration of 300 μg DDAVP intranasally by spray on 5 different occasions.Plasma levels of DDAVP showed a clear dose-response with the maximum levels at 0.4 μg/kg i.v. The effect of the spray approximated the 0.2 μg/kg response. However, the maximum response in both F VIII/vWF complex and plasminogen activator release was obtained after 0.3 μg/kg i. v. The response to 0.4 μg/kg i. v. was not significantly different from the response to 0.3 μg/kg indicating that maximum stimulation was reached with 0.3 μg/kg. There was no correlation between plasma levels of F VIII/vWF and DDAVP indicating that the biological response to DDAVP is subjected to saturation kinetics.The reproducibility of the effect of the spray dose on VIII : C was 21% (c.v.) and 27% for the intra-individual and interindividual variation, respectively, and compared favorably with intravenous administration.Intranasal DDAVP (300 μg) is as effective as 0.2 μg/kg intravenously and provides an accurate, reproducible and convenient alternative to parenteral administration.
Keywords: DDAVP; Intranasal; Intravenous; Pharmacokinetics; F VIII